Pengaruh Pemberian Penyuluhan Gizi Menggunakan Media Video tentang Higiene Sanitasi dalam Pengolahan Makanan terhadap Tingkat Pengetahuan dan Sikap Penjamah Makanan pada Aulia Catering Service di Kota Palangka Raya: Determine the Effect of Providing Nutritional Counseling Using Video Media about Sanitary Hygiene in Food Processing on the Level of Knowledge and Attitudes of Food Handlers at Aulia Catering Service in Palangka Raya City - Anggun Istiva Rahayu; Munifa Munifa; Juni Ramadhani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Food management in food services must apply the principles of food sanitation hygiene, from selecting food ingredients to presenting food to controlling risk factors for food contamination. Aulia Catering Service is one of the catering businesses located in Palangka Raya and is still running today. This study aims to determine the effect of providing nutritional counseling using video media about sanitary hygiene in food processing on the level of knowledge and attitudes of food handlers at Aulia Catering Service in Palangka Raya City. The design of this study is Pre Experimental Design with One Group Pre Test Post Test Design with a total sample of 20 people. The results of this study show that most of them are 60% female, 65% elderly, 60% high school education, 60% length of work and 65% length of work. The level of knowledge before is 50% good and 50% less; after counseling increases to 100% good. The attitude before 55% is good and 45% less; after counseling, it increases to 100% good. So it can be concluded that nutrition counseling using video media influences the knowledge and attitudes of food handlers at Aulia Catering Service in Palangka Raya City, with the result of a knowledge p-value of 0.002 and an attitude p-value of 0.003.